FAKTOR - FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014) - Linda Syafitri, 13.05.52.0265; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This research aims to analyze and provide empirical evidence of influence between executive compensation, institution ownershipâs share, profitability, independent commissioner, leverage, and auditing committee for tax aggressive to manufacturing companies that registered in BEI in 2011 until 2014. The population in this research are the manufacturing companies listed on the Indonesia Stock Exchange 2011-2014. Data was collected using purposive sampling method for manufacturing companies listed on the Indonesia Stock Exchange. Data were analyzed using multiple regression analysis. Regression results show that executive compensation, profitability, and auditing committee have negative significant effect on tax aggressive. Institution ownershipâs share, independent commissioner and leverage donât have significant effect on tax aggressive.Keywords: Executive Compensation, Institution Ownershipâs Share, Profitability, Independent Commissioner, Leverage, Auditing Committee, Tax Aggressive